A novel metal–organic frameworks assembled by one angular ligand and 5-aminoisophthalic acid: Synthesis, structure, electrochemical and photocatalytic properties. (1st August 2019) - Zhang, Xiaoyin; Zhang, Xia; Fan, Chuanbin; Zong, Ziao; Zhang, Dongmei; Luo, Qingdan; Bi, Caifeng; Fan, Yuhua
Graphical abstract: One novel metal–organic frameworks (MOFs) has been successfully synthesized under solvothermal condition and characterized by single crystal X-ray diffraction. The electrochemical behaviors of the complex have been studied in 0.1M KOH. Photocatalytic properties have been confired by degrading rhodamine B (RhB), methylene violet (MV), and methylene blue (MB). Possible degradation mechanism and the effect of the variables have been discussed. Abstract: One novel metal–organic frameworks (MOFs) constructed by one angular ligand and 5-aminoisophthalic acid, namely {[Ni(L)(bpt)(H2 O)]·2H2 O} n (H2 L = 5-aminoisophthalic acid, bpt = 2, 5-bis(4-pyridyl)-1, 3, 4-thiadiazole) has been designed and successfully synthesized under solvothermal condition. This compound was characterized by single crystal X-ray diffraction, elemental analysis, IR spectra, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). Single-crystal X-ray diffraction analysis reveals that the compound possesses a uninodal 3-connected 3D (three-dimensional) hcb topology framework with the point symbol (6 3 ). The thermal stabilities and electrochemical behavior in the solid state of the compound have been investigated in detail. Moreover, the photocatalytic degradation of the compound has been investigated. The results show photocatalytic activity of the compound for three dyes is MB > MV > RhB.